Models of Causal Factors Influencing Online Food Consumers’ Loyalty - Khongkhaluang, Duangjai; Tanyong, Pongsan; Wichayawong, Wallapa (Journal of Multidisciplinary in Humanities and Social Sciences, 2023)
This article aimed to (1) investigate the causal factors influencing online food consumers’ loyalty, and (2) investigate the guidelines to build online food consumers’ loyalty. The research model used mixed-methods research. For the quantitative research, the instrument was a questionnaire. The sample were 240 online food consumers that were selected by quota sampling. The data was analyzed using descriptive and inferential statistics. For the qualitative research, a semi-structured interview was used. The eight key informants were online food business operators that were selected by purposive sampling. The data were analyzed by content analysis and written in descriptive description. The research results were found as follows: 1) The E-service quality influences the customer’s loyalty statistically insignificantly at -0.04 It had a direct influence on trust at 0.89. The trust had statistically significant influence on online food customer’s loyalty at 0.96 and the E-service quality significantly influence on the customer’s loyalty through trust at 0.85. The structural equation had 76% of the predictive power of loyalty. And 2) Guidelines for building online food consumers’ loyalty stated that entrepreneurs should prepare and arrange food to be appetizing. There should be a wide variety of food menus. The amount of food is suitable for the price. The quality should be consumer’s expectation. It should have clearly defined communication channels, include the time of service, adhere to the principle of good service, and make an impression through speed, politeness, and ongoing promotions. There should be a system for checking orders, receiving complaints, and being ready to solve the problems, taking responsibility for any mistakes through various forms of compensation. The findings of the research on e-service quality and trust will be helpful in improving online food consumers’ loyalty business for entrepreneurs in Thailand.